In-Situ Study of Microstructure Evolution of Spinodal Decomposition in an Al-Rich High-Entropy Alloy - Jorgensen, Cameron S.; Santodonato, Louis J.; Littrell, Kenneth C.; Kuo, Chih Hsiang; Lee, Chanho; Unocic, Raymond R.; Liaw, Peter K.; Gilbert, Dustin A.; DeBeer-Schmitt, Lisa M. (Frontiers in Materials, 2022)
High-entropy alloys (HEAs) are materials which leverage the entropy of mixing to motivate the formation of single-phase solid solutions, even of immiscible elements. While these materials are well-recognized for their application to structural engineering, there is increasing interest in the use of HEAs for functional applications such as memory storage and energy devices. The current work investigates the HEA Al1.3CoCrCuFeNi, which has been previously shown to be single-phase at high temperatures, but undergoes phase separation at lower temperatures, transforming the structural and the functional properties. This phase separation is investigated at high temperatures with in-situ small angle neutron scattering (SANS) and scanning transmission electron microscopy (EDS). These techniques show that increasing the temperature up to 800°C, the microstructure of the HEA adiabatically disorders and abruptly homogenizes near 700°C, which is consistent with spinodal decomposition. Overall, the microstructural evolution proceeds mainly by the atomistic redistribution of the constituent elements within simple crystal lattices, producing coherent phase mixtures.